(untitled) (Journal of Physical Education (Maringá), 2016)
This article, based on a new theoretical approach, focuses on data from Basso (2012), the primary objective of which was to qualitatively validate courseware on Olympic Education . Specifically, notes made by teachers involved in validating the courseware are analysed, in particular where they point to the need for a greater number of practical activities in the courseware. The concepts of Santos (1993) and Hall (2006) that address the issue of identity by difference are used in this analysis. Those authors’ work will be used as a basis to analyse the notion of identity attributed to the discipline of physical education in the teachers’ notes and the consequence of this identity for the construction of Olympic Education courseware for this curriculum component.